Iranian Reliefs through the Eyes of Western Travelers (14th–19th Centuries) - Castelluccia, Manuel (Actual Problems of Theory and History of Art, 2021)
From the early 14th century, European travelers became acquainted with ancient Iranian monuments, especially those of the pre-Islamic Iranian kingdoms, such as the Achaemenid and Sasanian empires. Artistic representations dating to these periods included mainly reliefs carved on natural rocks or adorning royal buildings and tombs.Many of them were intentionally placed on cliffs overlooking important communication and trade routes, intended to be seen by all travelers. These reliefs, widespread throughout the Iranian Plateau, were the main visual expression of the conception of kingship and power by ancient Iranian ideology.The present contribution aims at exploring the different approaches of European travelers between the 14th and 19th century for the analysis and interpretation of rock-reliefs and architectural sculpture. It is particularly interesting to notice the development of Western attitudes towards ancient Persian monuments, since their discovery coincided with the development of European culture, mentality, politics, and economy over several centuries.
Keywords: Iranian art; relief; Achaemenid; Sasanian; Persepolis; Behistun